GE_GERICHTE P/12562/2017 vom 10. September 2018 - GE Cour de justice (2018)
SÉJOUR ILLÉGAL ; FIXATION DE LA PEINE ; CONCOURS D'INFRACTIONS ; PEINE COMPLÉMENTAIRE | LEtr.115.al1.letb; LEtr.119.al1; CP.47; CP.49.al1; CP.49.al2